The influence of family history of cardiovascular disease on blood pressure, waist hip ratio and body mass index in adolescents - Bansal, Utkarsh; Raja, Aakash; Agarwal, Prashant; Rathoria, Ekansh; Gupta, Abhishek; Gupta, Nyay Bhai; Agarwal, Shwinka (International Journal of Contemporary Pediatrics, 2020)
Background: Cardiovascular Diseases (CVDs) are the major cause of mortality in the world. Reducing the incidence of CVDs has been a challenge due to the multifactorial risk profile of their origin. Among the non-modifiable risk factor for CVDs family history holds a lot of importance. Objective of the study was to study blood pressure, waist hip ratio and body mass index among adolescents and verify the possible the relation with a family history of cardiovascular disease. Methods: This is a cross-sectional study, which was conducted in 286 school children aged 10 to 19 years, of either sex, from Barabanki. After getting consent from school authorities, children and their parents, a detailed history was taken with a pre-designed proforma. Anthropometric and blood pressure measurements were taken. Results: In the presence of any risk factor of CVDs, 33.9% of the adolescents were overweight/obese, 45.8% had abdominal obesity, 26.3% had elevated systolic BP and 35.6% had elevated diastolic BP. The group with family history of CVDs had significantly higher number of adolescents with obesity and/or hypertension. Conclusions: The present studied showed an important association between family history of CVDs and blood pressure, waist hip ratio and body mass index in adolescents.